(untitled) (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Mushrooms are considered as a valuable source of important nutrients having hepatoprotective and anti-hyperlipidemic actions. Present experimental research was done to explore the beneficial role of mushroom on health in hypercholesterolemia. Total thirty Swiss albino mice were taken and randomly divided into three groups: control A, group B and group C. Each group consisted of ten mice. The control A group was fed with normal mice pellet and fresh water. Group B was fed with hypercholesterolemic diet and group C was supplied hypercholesterolemic diet with mushroom powder (500g/kg/mice body weight) for 60 days. After the experimental tenure, mice of each group were sacrificed ethically and the samples (liver and blood) were collected for gross, histological study and lipid profile analysis.Â Increased liver weight, pale and hemorrhagic liver in gross observation along with some histological changes including dilation and congestion of central and portal vein, fat accumulation in hepatocyte and marked lymphocytic infiltration were found in group B, while mushroom supplementation recovered this gross and histological changes and reduced liver weight in group C. Just mild congestion and dilation was in the portal vein of group C. In lipid profile analysis, total cholesterol (TC), triglyceride (TG) and low density lipoprotein (LDL) level significantly reduced respectively by 10%, 38% and 17% in group C than group B. High density lipoprotein (HDL) level also significantly increased by 20% in group C compared to group B. Therefore, it can be concluded that mushrooms might have potentially beneficial actions in recovering of some complications in hypercholesterolemia.